Optimization of municipal solid waste air gasification for higher H2 production along with the validation via kinetics and statistical approaches. (15th August 2022) - Jamro, Imtiaz Ali; Chen, Guanyi; Baloch, Humair Ahmed; Wenga, Terrence; Ma, Wenchao
Graphical abstract: Highlights: MSW was investigated for an optimum H2 production through air gasification. The reaction temperature was dominated towards optimum H2 production. Optimum H2 production of 45.79 mol% was produced. Kinetic and statistical parameters showed a good agreement of the results. Abstract: This study aimed to investigate municipal solid waste (MSW) gasification to produce hydrogen (H2 ) at optimum levels. Therefore, the gasification of MSW was initially investigated using a thermogravimetric analyzer (TGA) coupled with mass spectrometer (MS). The leading gases detected by the MS included; H2, CO, CO2, and CH4 . Afterward, the gasification was carried out in the tubular batch reactor to investigate the composition, gasification products, and syngas properties (H2 /CO molar ratio, H2 + CO, lower heating value (LHV), H2 yield)) under some influencing parameters. Due to the dominating reaction temperature, a significant increase in H2 (25.41% to 39.70%) and gas (57.10–74.93%) production accompanied a notable decrease in tar (16.48–8.54%) and char (28.40–15.52 wt%) contents. Flynn-Wall-Ozawa (FWO) and central composite design (CCD) models were applied to investigate kinetic and statistical parameters which showed better results. Optimum H2 production of 45.79 mol% with H2 /CO, H2 + CO, LHV, and yield of 1.78, 72.78 mol%, 9.96 MJ/Nm 3, and 13.83 mol kg-MSW −1 respectively was obtained at optimal temperature, particle size, and heating rate of 703.49 ℃, 3.21 mm, and 5 ℃/min respectively, which can be an appropriate fuel for Fischer Tropsch process for manufacturing of transportation fuels.